Defining Endotheliopathy in Murine Polytrauma Models. Issue 6 (June 2022) - Wallen, Taylor E.; Singer, Kathleen E.; Elson, Nora C.; Baucom, Matthew R.; England, Lisa G.; Schuster, Rebecca M.; Pritts, Timothy A.; Goodman, Michael D.
ABSTRACT: Introduction: "Endotheliopathy of trauma" is recognized as endothelial dysfunction following traumatic injury leading to poor patient outcomes. Acute post-traumatic disruptions in endothelial cell function have been associated with profound physiologic, hemodynamic, and coagulation derangements. The goal of this study was to define the generation and extent of endotheliopathy in murine polytrauma models by evaluating the post-traumatic release of serum biomarkers of ongoing cellular injury. Methods: Mice were randomized to undergo moderately severe concussive TBI by weight drop, 60-min hemorrhagic shock to MAP 25 mmHg with subsequent resuscitation with Lactated Ringer's, submandibular bleed (SMB), and/or midline laparotomy with rectus muscle crush. Mice were sacrificed at 1, 4, or 24 h for serum biomarker evaluation. Results: Serum biomarkers revealed differential timing of elevation and injury-dependent release. At 24 h, soluble thrombomodulin was significantly elevated in combined TBI + shock + lap crush compared to untouched, and shock alone. Syndecan-1 levels were significantly elevated after shock 1 to 24 h compared to untouched cohorts with a significant elevation in TBI + shock + lap crush 24 h after injury compared to shock alone. UCHL-1 was significantly elevated in shock mice at 1 to 24 h post-injury compared to untouched mice. UCHL-1 was also significantly elevated in the TBI + shock cohort 24 h after injury compared to shock alone. Hyaluronic acid release at 4 h was significantly elevated in shock alone compared to the untouched cohort with further elevations in TBI + shock + lap crush and TBI + shock compared to shock alone at 24 h. Hyaluronic acid was also increased in lap crush and laparotomy only cohort compared to untouched mice 24 h after injury. Conclusions: A murine model of polytrauma including TBI, hemorrhagic shock, and laparotomy abdominal crush is a reliable method for evaluation of endotheliopathy secondary to trauma as indicated by differential changes in serum biomarkers.